Carrying Across or Pulling down? Understanding Translation through its Metaphors: A Cross-linguistic Perspective - Šeškauskienė, Inesa (Respectus Philologicus, 2020)
The paper investigates how translation is conceptualised through metaphors employed in academic texts in English and Lithuanian focusing on translation problems. As established by previous research, metaphors are tools of rendering abstract thought in terms of more concrete experiences. The methodology of this investigation is based on the Conceptual Metaphor Theory and further development in metaphor research, the main principles of Metaphor Identification Procedure and metaphorical patterns. The results suggest that English tends to more frequently conceptualise translation as human and also as a dynamic activity, whereas Lithuanian opts for more static conceptualisation of translation in terms of object and material. Such tendencies might be linked, among other factors, to very different etymologies of the verb ‘translate’ and its derivatives in English and Lithuanian as well as other senses of the word.